A phase 1 clinical trial evaluating marizomib, pomalidomide and low‐dose dexamethasone in relapsed and refractory multiple myeloma (NPI‐0052‐107): final study results. (26th October 2017) - Spencer, Andrew; Harrison, Simon; Zonder, Jeffrey; Badros, Ashraf; Laubach, Jacob; Bergin, Krystal; Khot, Amit; Zimmerman, Todd; Chauhan, Dharminder; Levin, Nancy; MacLaren, Ann; Reich, Steven D.; et al.
Summary: Marizomib (MRZ) is an irreversible, pan‐subunit proteasome inhibitor (PI) in clinical development for relapsed/refractory multiple myeloma (RRMM) and glioma. This study analysed MRZ, pomalidomide (POM) and low‐dose dexamethasone (Lo‐DEX) [PMD] in RRMM to evaluate safety and determine the maximum tolerated dose (MTD) and/or recommended Phase 2 dose (RP2D). Intravenous MRZ (0·3–0·5 mg/m 2 ) was administered over 2 h on days 1, 4, 8, 11; POM (3–4 mg) on days 1–21; and Lo‐DEX (5 or 10 mg) on days 1, 2, 4, 5, 8, 9, 11, 12, 15, 16, 22 and 23 of every 28‐day cycle. Thirty‐eight patients were enrolled that had received a median of 4 (range 1–10) prior lines of therapy; all patients received prior lenalidomide and bortezomib. No dose‐limiting toxicities (DLTs) were observed and 0·5 mg/m 2 MRZ was determined to be the RP2D. The most common treatment‐related ≥Grade 3 adverse events were: neutropenia (11/38 patients: 29%), pneumonia (4/38 patients 11%), anaemia (4/38 patients; 11%) and thrombocytopenia (4/38 patients; 11%). The overall response rate and clinical benefit rate was 53% (19/36) and 64% (23/36), respectively. In conclusion, PMD was well tolerated and demonstrated promising activity in heavily pre‐treated, high‐risk RRMM patients.